LIPID PEROXIDATION IN THE CORRECTION OF THEIR PREPARATION FIRUTAS (Web of Teachers: Inderscience Research, 2026)
One of the important aspects of studying the pathogenesis of various diseases is the study of the state of lipid peroxidation and the antioxidant system. The disruption of the stationary state of free-radical oxidation is considered one of the universal, non-specific indicators of damage and is characteristic of a wide range of diseases, including atherosclerosis, stress, neuroses, diabetes mellitus, inflammatory processes, autoimmune diseases, and others. (3,5,6,8,9,10).